2022
DOI: 10.35899/biej.v4i2.367
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kompensasi Terhadap Kepuasan Kerja Karyawan (survey pada Divisi Production Planning and Control Di PT Sumi Rubber Indonesia)

Abstract: This study aims to determine the effect of compensation on job satisfaction for employees of PT Sumi Rubber Indonesia. This study uses questionnaires to obtain data that has been distributed to 212 employees of PT Sumi Rubber Indonesia. The questionnaire that has been distributed consists of 20 statement items using five (5) Likert scales. The analytical technique used in this research is descriptive analysis which is used to analyze the effect of compensation on job satisfaction for employees of PT Sumi Rubbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Of course, in obtaining high compensation, expertise, skills, and also high positions and responsibilities are needed as well. This is in accordance with research conducted by Hakim et al [41], which found that compensation has a positive effect on employee job satisfaction, where the higher the compensation received by employees, the higher the satisfaction felt in working compensation such as salaries and incentives. Therefore, positions at the managerial level in this study have high job satisfaction due to the large compensation factor as well.…”
Section: Discussionsupporting
confidence: 92%
“…Of course, in obtaining high compensation, expertise, skills, and also high positions and responsibilities are needed as well. This is in accordance with research conducted by Hakim et al [41], which found that compensation has a positive effect on employee job satisfaction, where the higher the compensation received by employees, the higher the satisfaction felt in working compensation such as salaries and incentives. Therefore, positions at the managerial level in this study have high job satisfaction due to the large compensation factor as well.…”
Section: Discussionsupporting
confidence: 92%